Pendekatan Historis Psikologis Pada Musik “Bahagia Lagi” Karya Piche Kota - Muhammad Luthfi Hassana; Frisca Nayla Putri; Mufidatul Yuliana Mustika; Alfiana Nur Hayati; Meris Gusmahvida (sarasvati, 2026)
This study aims to analyze the lyrics of the song “Bahagia Lagi” by Piche Kota through a historical-psychological approach to uncover the emotional dynamics and psychological structures embedded within the text. This research employs a qualitative method with a library research design, utilizing song lyrics as primary data and scholarly literature as secondary data. The analysis is conducted using content analysis techniques, including text segmentation, thematic coding, psychological interpretation, and historical contextualization. The findings reveal that the song does not merely represent emotional recovery or happiness after relational conflict. Instead, it reflects complex psychological dynamics, including emotional dependency, denial, cognitive dissonance, and maladaptive coping. The notion of happiness constructed in the lyrics functions as a psychological defense mechanism rather than an authentic emotional condition. From a historical perspective, this phenomenon aligns with contemporary trends in popular music that emphasize “healing” narratives as a form of emotional expression. This study contributes to literary and cultural studies by offering a critical interpretation of popular song lyrics through an integrated historical and psychological framework. It also challenges the assumption that representations of happiness in texts necessarily reflect genuine emotional states.